Psychological Resilience Among Older Japanese Adults With Mild Cognitive Impairment During the COVID-19 Pandemic - Matsumoto, Nanae; Sugimoto, Taiki; Kuroda, Yujiro; Uchida, Kazuaki; Kishino, Yoshinobu; Arai, Hidenori; Sakurai, Takashi (Frontiers in Psychiatry, 2022)
Psychological resilience refers to the ability to cope with adversities, and deficits in resilience might lead to mental illness. The COVID-19 pandemic has had impact on psychological resilience for older adults, but there are as yet no data on its impacts on the mental health of older adults who were living with mild cognitive impairment (MCI). Therefore, the aim of this study was to investigate the impact of the COVID-19 pandemic on psychological resilience in older adults with MCI and to explore associated physical and psychosocial factors. In this cross-sectional study of 268 older adults aged 65–85, we defined MCI as age- and education-adjusted cognitive decline with a standard deviation of 1.0 or more from the reference threshold. During December 2020 to April 2021, we carried out to all participants the 10-item version of the Connor-Davidson Resilience Scale (CD-RISC-10) to measure psychological resilience. We also conducted a comprehensive geriatric assessment including sleep quality and depressive symptoms (Pittsburgh Sleep Quality Index and 15-item Geriatric Depression Scale, respectively). To identify factors associated with CD-RISC-10 scores (mean: 23.3 ± 0.4), multiple regression analysis revealed that older age [coefficient = 0.23, 95% confidence interval (CI) = 0.06–0.39] was significantly correlated with higher scores, whereas poor sleep quality (coefficient = −2.06, 95% CI = −3.93 to −0.19) and depressive symptoms (coefficient = −2.95, 95% CI = −5.70 to −0.21) were significantly correlated with lower scores. In this study, older adults with MCI showed low psychological resilience during the COVID-19 pandemic, and people with low psychological resilience indicated poor sleep quality and depressive symptoms. Our findings suggest directions for devising interventions to maintain mental health and psychological resilience among the vulnerable population of older adults with MCI living under the socially isolated conditions of COVID-19 pandemic restrictions. Our recommendation includes continuous assessment of this population and appropriate care for poor sleep quality and depressive symptoms.